2019
DOI: 10.5334/ijc.888
|View full text |Cite
|
Sign up to set email alerts
|

Can Micro-Irrigation Technologies Resolve India’s Groundwater Crisis? Reflections from Dark-Regions in Gujarat

Abstract: Upfront capital costs of micro-irrigation technologies are subsidized across the dark-zone regions of the state of Gujarat, where groundwater was observed as over-extracted, with an anticipation that wide-scale adoption could perhaps reduce pressure on the aquifer. From a macro-perspective, the real water saving potential depends on not only adoption of these technologies but also how best the farmers' get convinced about the looming water scarcity and try to adapt to the new technologies. While there are seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…the Ganga Kalyana Scheme for tribal populations in Karnataka or the subsidy and power connection policies in dark-regions in Gujarat 84 . The other limit is indeed the “rebound effect” associated with micro-irrigation: at the individual level, the farmers who possess this equipment seek to use the water they save to irrigate new areas 85 , 86 . The pressure on water thus remains unchanged, or even increases, exacerbating the impact on unequipped irrigators, and in no way resolves the issue of equity.…”
Section: Discussionmentioning
confidence: 99%
“…the Ganga Kalyana Scheme for tribal populations in Karnataka or the subsidy and power connection policies in dark-regions in Gujarat 84 . The other limit is indeed the “rebound effect” associated with micro-irrigation: at the individual level, the farmers who possess this equipment seek to use the water they save to irrigate new areas 85 , 86 . The pressure on water thus remains unchanged, or even increases, exacerbating the impact on unequipped irrigators, and in no way resolves the issue of equity.…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of the PIM Act coincided with the wide-scale promotion of micro irrigation schemes, which was supported by the state under the national initiative National Mission on Micro Irrigation since May 2005. The programme benefited vast tracks of farm lands covered under the private and public tube wells (Bahinipati & Viswanathan, 2019a, b). The dramatic increase in area under MIS has been facilitated by the Gujarat Green Revolution Company (GGRC) ably supported by the national and state governments (GoG, 2020).…”
Section: Water Policy Reforms and Their Impacts In Gujarat: An Overviewmentioning
confidence: 99%
“…While the demand for water had increased over time, the state has been facing problems of depletion of groundwater resources as well as stagnation of area under surface irrigation systems along with a progressive shift towards adoption of water saving irrigation systems (Bahinipati & Viswanathan, 2019a, b). The Falkenmark measure of water stress suggests that ‘if per capita water availability is below 1,000 m 3 , it depicts water scarcity and as per this criterion, Gujarat is considered as ‘water starved’ in view of the low per capita rainwater availability than other states.…”
Section: Introductionmentioning
confidence: 99%
“…Bahinipati and Viswanathan (2019a) observed that pecuniary benefits associated with MIS, rather than concerns on real savings in water, enhanced its adoption, even in the dark-zone regions in Gujarat. As a result, the observed large-scale adoption of MIS did not reduce the pressure on groundwater extraction (Bahinipati & Viswanathan, 2019b).…”
Section: Climate-resilient Agriculture: Global Trends and Practicesmentioning
confidence: 99%